Toward and Beyond APEC Summit 2015: Key Issues and Challenges of Professional Service Mobility - Aniceto Jr. C. Orbeta; Kathrina G. Gonzales; Stephanie Rose E. Flores (Philippine Institute for Development Studies (PIDS), 2015)
Labor mobility or professional service mobility, in particular, has become increasingly important. Its prevalence (in terms of volume of jobs) in trade in services and its economic contribution to the Asia-Pacific Economic Cooperation (APEC) and other regional trading blocs is increasing. However, as appropriately noted in the General Agreement of Trade in Services (GATS), the movement of natural persons continues to have barriers due to misconceptions and political issues. In this study, the importance of and barriers to professional service mobility are explained and emphasized in the hopes of making this a priority issue in the upcoming APEC Summit in 2015.During the study's focus group discussion (FGD), the APEC Human Resources Development Working Group (HRDWG) provided recommendations through these main points: (1) Professional service mobility is not synonymous to migration given its impermanence and that the relationship is between a foreign employer and an intermediary; (2) Skilled workers pertain to those bearing professional licenses while unskilled (lower skilled) workers pertain to blue-collared workers, but such distinction must be scrapped; and (3) Education/training is deemed as very important by all sectors of society as indicated by the preference for professional workers over lower-skilled workers.The study recommends that a comprehensive discussion related to professional service mobility be one of the priorities in the APEC 2015 summit, in particular covering topics such as the APEC-wide Qualifications Referencing Framework, guiding principles in country-to-country labor policies, human capital management, and the systematic collection of good labor statistics.
Keywords: 330; labor mobility; professional service mobility; APEC Summit 2015